A case report of periprosthetic fracture left proximal humerus with radial nerve palsy following pectoralis major repair. Issue 6 (22nd April 2015) - Shah, Jaydeep; Marson, Ben A.
Key Clinical Message Primary repair of pectoralis major tendon with bony tunnels and anchor sutures in the proximal humerus creates a potential weakness and stress riser leading to increased risk of periprosthetic fracture and nerve damage at the site of weakness with subsequent injury, if not allowed to heal satisfactorily with adequate period of rest.